The Role of Adele T. Katz in the Early Expansion of the New York "Schenker School" - Berry, David Carson (Current Musicology, 2002)
In 1927, Heinrich Schenker named New York as the first North American city in which his ideas were spreading, though he was not specific as to the means of transmission.l Four years later, however, the chief point of con-tact would be clear, as Schenkerism found an institutional home at the David Mannes Music School (now Mannes College of Music) . It was there that Schenker’s student Hans Weisse began teaching in 1931; starting the next year, he concurrently conducted graduate seminars at Columbia Uni-versity. Mter Weisse’s untimely death in 1940, Schenker’s student Felix Salzer assumed similar duties at Mannes; he later became a professor of music at Queens College ofthe City University of New York.